(3QSGdI aj cdeI GdJhMjO hGdTgGOIs
(3ChdgG (B:s
(3CeG HYO aEf eG ojaJM Hg GdESdGe hjSJhVM Hg GdESJSdGe cdeI GdTgGOI hgj bhdfG CTgO Cf dG Edg EdG Gddg s
(3BNQgG (B:s
(3MGTjI TQM GdYbGFO dCMeO GdOjf GdHQOYj JeJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3HdOjI GdCScfOQjI (B(3182 (3L(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds